Structural health monitoring of a stress-ribbon footbridge - Wei-Hua Hu (2013)
This work describes the development and implementation of a structural health monitoring system on astress-ribbon footbridge. In a first part, it characterises the implemented continuous dynamic monitoringsystem and the application of automated operational modal analysis to analyse the variation of modalproperties estimates along several years. A correlation analysis is then conducted showing that environmentaland operational factors (e.g. temperature and pedestrian traffic) induce significant nonlineareffects on the modal frequency estimates, which may mask subtle early damage. Taking into account linearrelations between frequency estimates of different modes, the linear Principal Component Analysis(PCA) is applied to remove those effects. Novelty analysis of the residual errors of PCA is used to builda statistical damage indicator for long term structural health monitoring. Finally, the efficiency of thedescribed damage detection methodology is evidenced by simulating some realistic damage scenariosbased on an experimentally validated finite element model and observing the clear deviation of the damageindicator. It is demonstrated that such a dynamic monitoring system can serve as an effective tool forlong term bridge health monitoring.